Price Elasticities and Tax Reform in Mexico - Nicita, Alessandro (2012)
Price responses are usually estimated for the average household. However, different households are unlikely to respond in a similar way to movement in prices. Consequently, relying on averages may be misleading when examining the behaviour of a particular group of households such as the poor. This article uses six household surveys collected in Mexico between 1989 and 2000 to derive price responses for 10 product groups and for five levels of income households. The estimated price elasticities are then fed into a micro simulation model to measure the effect of a marginal tax reform. The results find that that poorer households tend to react substantially more to movement in prices, suggesting the usefulness of estimating elasticities that reflect the behavioural responses of the poor rather than of the entire population. The micro simulation results indicate that reducing the taxes on maize, alcoholic beverages and vegetables would be both more equitable and more efficient in terms of social welfare. Meanwhile, a reduction in the tax on legumes, sugar, and oils and fats, while inefficient, would contribute to reduce inequality.